Performing sentiment analysis in Bangla microblog posts - Chowdhury, Shaika; Chowdhury, Wasifa (© 2014 IEEE Computer Society, 2017)
This conference paper was presented in the International Conference on Informatics, Electronics and Vision, ICIEV 2014; Dhaka; Bangladesh; 23 May 2014 through 24 May 2014 [© 2014 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICIEV.2014.6850712